Zero-waste approach in municipal solid waste incineration: Reuse of bottom ash to stabilize fly ash. (1st February 2020) - Assi, Ahmad; Bilo, Fabjola; Zanoletti, Alessandra; Ponti, Jessica; Valsesia, Andrea; La Spina, Rita; Zacco, Annalisa; Bontempi, Elza
Abstract: In this paper a simple method for all waste recovery through municipal solid waste incineration (MSWI) is presented. For the first time, MSWI fly ash (FA) is treated using MSWI bottom ash (BA), which is considered as a new urban mining source due to its pozzolanic characteristics. The proposed technology involves mixing these ashes with two other components: flue gas desulphurization residue and coal fly ash. Thermal annealing at a low temperature (120 °C for 4 h) can also be performed, to accelerate some reactions, but it is not necessary for stabilization. The efficacy of the process is demonstrated by the comparison of elemental concentrations in leaching solutions that are detected in the untreated ashes and the obtained stabilized materials, which show the reduced solubility of leachable Zn and Pb (with respect to the starting MSWI FA). The chemical, morphological, and structural characterization of the obtained materials makes it possible to propose and discuss a stabilization mechanism, which was attributed to carbonation and formation of calcium silicate hydrate (C–S–H). In particular, for the stabilized sample, X-ray Diffraction analysis confirmed the formation of calcite, whereas the sample morphology shows some fibrils that may be due to amorphous C–S–H with a Ca/Si ratio that is slightly smaller than 1.5. Because the proposed method employs wastes produced at the same location, it is reasonable to conclude that the method may be directly applied to incinerator plants due to the simplification of the MSWI FA waste management strategy, which generally involves its transport and stabilization treatment before landfilling. Finally the saved carbon dioxide emissions and the economic benefits that are a result of the new urban mining proposed approach have been evaluated for Europe. In particular the avoid of MSWI FA landfilling was evaluated to save approximately 1.6 M€/day, and the saved carbon dioxide emissions introduced into the atmosphere is approximately 960 kt/year. Highlights: A new urban mining strategy for MSWI FA stabilization is proposed. Reuse of the finest BA parts is suggested due to their amorphous components. Pb and Zn stabilization occurred because of carbonation and pozzolanic reactions. This treatment technology may be directly applied to incinerator plants. The proposed approach fulfils the requirements of a circular economic policy.